Optimalisasi Focus Group Discussion untuk Meningkatkan Pemahaman Kritis Siswa SMPN 03 Kalipare terkait Pernikahan Dini - rojah, fika (Maliki Interdisciplinary Journal, 2025)
The social issue of early marriage in Putukrejo Village motivated the implementation of socialization activities and focus group discussions (FGD) for this study. The research targeted students of SMPN 03 Kalipare, Putukrejo Village, consisting of all seventh, eighth, and ninth graders. The method applied was FGD, carried out in three stages: pre-FGD, FGD implementation, and post-FGD. The results show that the students successfully identified the factors contributing to early marriage, the psychological and social impacts faced by those involved, and possible solutions to prevent and address early marriage. Throughout the process, the FGDs fulfilled the stages of critical thinking, including problem identification, analysis, evaluation, and formulation of alternative solutions.